Trastornos de la lactancia materna y otros factores asociados a la pérdida de peso neonatal excesiva en un hospital de la Seguridad Social en Lima, Perú - Berger Larranaga, Melissa (2016)
INTRODUCTION: during the first days of life the mother is the main source of nutrients for the newborn. However, breastfeeding difficulties are common and may generate excessive neonatal weight loss. OBJECTIVE: estimate the magnitude and association between breastfeeding problems and excessive neonatal weight loss beyond the physiological norm in the neonatology ward in a social security hospital in Lima, Peru. METHODS: we conducted a cross sectional analysis of the recorded neonatal weight in a routine evaluation (between 24 and 72 hours of life) and compared it against birth weight. Excessive weight loss was defined as a difference greater than or equal to 7 %. Breastfeeding problems (defined as problems with breastfeeding initiation, mouth position, breastfeeding duration, breastfeeding frequency, too much clothing, nipple pain and C form) were investigated using a survey and visual verification. The association between excessive weight loss and breastfeeding problems, adjusted by other factors, was quantified using a multiple generalized linear model. RESULTS: excessive weight loss was present in 18.8% (74/393) of the newborns. Improper positioning of the mouth on the nipple was present in 53.7% (211/393) of neonates while nipple pain was reported by 44.0% (173/393) of mothers. In the adjusted analysis, nipple pain [PR = 1.50 (95% CI: 1.02 to 2.22)] and improper positioning of the mouth [PR = 1.67 (95% CI: 1.09- 2.57)] were associated with an increased occurrence of excessive neonatal weight loss. CONCLUSIONS: breastfeeding problems are common. These difficulties are significantly associated with an increased occurrence of excessive neonatal weight loss. Improvements in breastfeeding practices, for example through educational programs, may decrease the occurrence of excessive neonatal weight loss.